The Role of Selectively Located Commercial Graphene Nanoplatelets in the Electrical Properties, Morphology, and Stability of EVA/LLDPE Blends. Issue 9 (3rd July 2018) - Kurusu, Rafael S.; Helal, Emna; Moghimian, Nima; David, Eric; Demarquette, Nicole
Abstract: Graphene nanoplatelets (GN) produced on a large scale by mechanochemical exfoliation of graphite are incorporated in a co‐continuous ethylene‐vinyl acetate/linear low‐density polyethylene (EVA/LLDPE) blend. Two different processing routes are chosen to selectively place GN in the EVA phase or force its migration to the EVA/LLDPE interface. The results show a drastic decrease in the electrical percolation threshold when the blends are compared to the respective single‐polymer composites. Even with the presence of agglomerates, GN particles are able to migrate to the blend interface and stabilize the morphology and hence the electrical properties. Annealing the insulating samples at processing temperatures causes a drastic increase in conductivity due to continued GN migration and blend morphology coarsening. Semi‐conductive samples, in which a more robust GN network is already established during processing, present no change in morphology but a slight increase in conductivity during annealing. The mechanical performance of the materials is also evaluated and some of the blends with GN present similar elongation at break as pure EVA, but with increased tensile modulus and tensile strength. The electrical performance at different working temperatures shows that the EVA/LLDPE/GN composites are good candidates to act as a semi‐conductive screen material in power cables or as anti‐static materials in electronic devices. Abstract : Commercial graphene nanoplatelets (GN) produced on a large scale are incorporated in a co‐continuous blend of linear low‐density polyethylene (LLDPE) and ethylene‐vinyl acetate (EVA) by melt‐mixing. GN is selectively located either in the EVA phase or at the interface between the two polymers, drastically reducing the electrical percolation threshold. The conductive GN network increases the stability of electrical properties and blend morphology at different temperatures.